Expression of centrosome-associated gene products is linked to tetraploidization in mantle cell lymphoma - Neben, Kai; Ott, German; Schweizer, Silja; Kalla, Jörg; Tews, Björn; Katzenberger, Tiemo; Hahn, Meinhard; Rosenwald, Andreas; Ho, Anthony Dick; Müller-Hermelink, Hans Konrad; Lichter, Peter; Krämer, Alwin (International journal of cancer, 2007)
In mantle cell lymphoma (MCL), a blastoid variant with a striking tendency to harbor chromosome numbers in the tetraploid range has been identified. Centrosome aberrations have recently been implicat...
Gesehen am 02.11.2021